В стране невыученных уроков - Гераскина Лия (Школьная библиотека, 2009)
Экземпляры: Ф. 2 (20191223) / Инвентарный номер: 45887 / Цена: 60.00 / Сис.шифр: 84(2=411.2) / Авт.знак: Г 37 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44